The impact of the circulation system on the concentration level of micropollutants in the swimming pool water treatment system - Anna Maria Lempart (Inżynieria Ekologiczna, 2018)
Each pool installation should ensure proper and constant circulation of water in a closed circuit system. However, the operation of such a system can potentially cause the accumulation of small-molecule micropollutants in the pool water treatment system. The aim of this work is to confirm or reject this argument. As part of preliminary tests, the content of organic and inorganic substances in swimming pool water was analyzed based on general indicators such as TOC, UV 254 absorbance and conductivity. In the main stage of the research, pool water samples collected from four different points of the swimming pool installation were subjected to chromatographic analysis to determine the small-molecule micropollutants. The tap water used to fill the basin and regular replenishment of volume losses was also tested. This study was intended to exclude the tap water as a potential source of contamination in the pool water. Preliminary studies have shown almost a two-fold increase in the total organic carbon content and absorbance UV 254 at the turn of six months, which undoubtedly indicates the accumulation of organic pollutants in pool water circulation systems. It was not observed in the case of inorganic compounds. As a result of the chromatographic analyzes of the pool water, the content of pharmaceuticals and personal care product was determined. It was found that the compensation tank is the place of the highest accumulation of the tested pharmaceuticals in the pool water treatment system , while the cosmetics component accumulated in the pool basin to the greatest degree. It was affected by the duration of the filter cycle.